Application of rice endophytic Bradyrhizobium strain SUTN9-2 containing modified ACC deaminase to rice cultivation under water deficit conditions. Issue 1 (1st January 2020) - Sarapat, Sukanlaya; Longtonglang, Aphakorn; Umnajkitikorn, Kamolchanok; Girdthai, Teerayoot; Boonkerd, Nantakorn; Tittabutr, Panlada; Teaumroong, Neung
ABSTRACT: Bacterial 1-aminocyclopropane-1-carboxylate (ACC) deaminase is a key factor for alleviating the plant ethylene biosynthesis, which is induced by stress. The ACC deaminase-improved strains of the rice endophytic Bradyrhizobium sp. SUTN9-2, SUTN9-2 (ACCDadap) and SUTN9-2:pMG103:: acdRS, exhibit 1.4- and 8.9-fold higher ACC deaminase activity than the wild type, respectively (Sarapat S, Songwattana P, Longtonglang A, Umnajkitikorn K, Girdthai T, Tittabutr P, Boonkerd N, Teaumroong N. 2020. Effects of Increased 1-Aminocyclopropane-1-Carboxylate (ACC) Deaminase Activity in Bradyrhizobium sp. SUTN9-2 on Mung Bean Symbiosis under Water Deficit Conditions. Microbes Environ. 35). The effects of these on rice growth under water deficit conditions were evaluated. The bacterial inoculations reduced ethylene synthesis, leading to a reduction in membrane destruction and the chlorophyll content of rice. Furthermore, the bacterial inoculations improved the leaf relative water content, survival, recovery rates, and improved the crop yield in field conditions. Therefore, the water deficit tolerance of rice was improved by controlling ethylene biosynthesis by improving ACC deaminase activity with endophytic SUTN9-2. Moreover, the SUTN9-2 (ACCDadap) strain can be used as a bio-inoculant under field conditions to enhance rice growth, grain yield, and enhance drought tolerance.